KEMAMPUAN NUMERASI SISWA SEKOLAH DASAR DITINJAU DARI JENIS KELAMIN - Mariamah, Mariamah; Suciyati, Suciyati; Hendrawan, Hendrawan (Program Studi Pendidikan Guru Sekolah Dasar, FKIP, Universitas Mulawarman, 2021)
Numerical ability is also the ability to use various kinds of numbers and symbols related to basic mathematics to solve everyday life problems, the ability to analyze information that is displayed in various forms (graphs, tables, charts, etc.). Unfortunately, reality shows that students' numeracy skills are not maximized. Based on the results of the Program for International Student Assessment (PISA) for Indonesia, mathematics scores are below average. According to Kompas.com, the average PISA score of OECD (The Organization for Economic Cooperation and Development) members has continued to decline over the last three years. Indonesia is ranked 74th out of 79 countries, while for the assessment of mathematical ability and scientific ability, Indonesia is ranked 73rd and 71st of the 79 participating countries. It was also found that the gender gap in performance inequality in learning performance between women and men is not large. Female students outperformed male students in all areas of PISA. This research is a descriptive research. To find out students' numeracy skills by using AKM questions. The research subjects were students at SDN Talabiu upper class (grade 4,5,6) as many as 36 people. Based on the research that has been done, based on the percentage of the results of the problem solving which is then adjusted to the category, the numeracy ability of female students is in the high category of 18%, while male students are 12.5%. This shows that the numeracy skills of female students are better than male students.